Shuffle the Decks: Children Are Sensitive to Incidental Nonrandom Structure in a Sequential-Choice Task. (April 2022) - Breslav, Alexander D. S.; Zucker, Nancy L.; Schechter, Julia C.; Majors, Alesha; Bidopia, Tatyana; Fuemmeler, Bernard F.; Kollins, Scott H.; Huettel, Scott A.
As children age, they can learn increasingly complex features of environmental structure—a key prerequisite for adaptive decision-making. Yet when we tested children ( N = 304, 4–13 years old) in the Children's Gambling Task, an age-appropriate variant of the Iowa Gambling Task, we found that age was negatively associated with performance. However, this paradoxical effect of age was found only in children who exhibited a maladaptive deplete-replenish bias, a tendency to shift choices after positive outcomes and repeat choices after negative outcomes. We found that this bias results from sensitivity to incidental nonrandom structure in the canonical, deterministic forms of these tasks—and that it would actually lead to optimal outcomes if the tasks were not deterministic. Our results illustrate that changes in decision-making across early childhood reflect, in part, increasing sensitivity to environmental structure.